Identifikasi dan Remediasi Miskonsepsi dengan Pendekatan Perubahan Konseptual pada Materi Kesetimbangan Kimia - Mayasri, Adean; Reza, Muhammad; Nasir, Muhammad (Chemistry Education Department of Education and Teaching Faculty, 2023)
Identifying misconceptions in chemistry learning is important to improve the quality of learning. The use of appropriate learning approaches is needed to correct students' misconceptions. This research aims to identify and remediate students' misconceptions about chemical equilibrium material by using a conceptual change approach. The method used was a quantitative-pre-experimental method with a one-group-pretest-posttest-design. The sampling technique was purposive sampling with number of samples was 63 student of eleventh grade. The instrument used was a four-tier diagnostic test based on CRI. Data was obtained by giving the tests to students twice, before and after the remediation of misconceptions using a conceptual change approach. Based on the results of identifying the initial level of students understanding, it was found that the category of understanding the concept about 41%, misconceptions about 41%, and did not understand the concept about 18%. Misconceptions with high criteria were identified in the equilibrium constant sub-material of about 65%. The remediation of misconceptions was carried out by using a conceptual change approach to chemical equilibrium material. The changes in students' understanding level are based on the average N-gain value, namely students' concept understanding of 0.77 in the high category, misconceptions of -0.79 in the decreasing category and not understanding the concept of -0.72 in the decreasing category. The reduction of high criteria misconceptions in the equilibrium constant sub-material with an N-gain value of -0.78 in the decreasing category. It was concluded that remediation using the conceptual change approach could reduce students' misconceptions.